2018
DOI: 10.1080/09513590.2018.1431769
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of l-carnitine improves the clinical outcome of fertility in patients with IVF treatment

Abstract: Age-dependent decline of mitochondrial function has been proposed to be a main cause of decline of embryo quality. Then, l-carnitine plays important roles in reducing the membranous toxicity of free-fatty acids by forming acyl-carnitine and promoting β-oxidation, preventing cell damage. Recent research revealed that l-carnitine played important roles in vitro in oocyte growth, oocyte maturation and embryo development. However, such beneficial effects of l-carnitine in vivo have yet to be verified. The effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In the present study, we have relied on a mouse DHEA model of PCOS to demonstrate that oral administration of acyl-L-carnitines alleviates ovarian dysfunctions associated with this syndrome and to explore whether the co-administration of PLC provides better activity. In order to select the proper protocol for LC and ALC administration we based on studies on male and female fertility [10,14,30,[35][36][37][38]. For PLC, since there are no studies on fertility, we employed the minimum effective dose identified by Delaney et al [39].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have relied on a mouse DHEA model of PCOS to demonstrate that oral administration of acyl-L-carnitines alleviates ovarian dysfunctions associated with this syndrome and to explore whether the co-administration of PLC provides better activity. In order to select the proper protocol for LC and ALC administration we based on studies on male and female fertility [10,14,30,[35][36][37][38]. For PLC, since there are no studies on fertility, we employed the minimum effective dose identified by Delaney et al [39].…”
Section: Discussionmentioning
confidence: 99%
“…33 Further, a clinical study reported that administration of Lcarnitine to patients who were previously failure to in vitro fertilization-embryo transfer, significantly improved the quality of embryo on Days 3 and 5 after insemination. 34 As coadministration with clomiphene citrate, we found that carnitine supplement could significantly improve ovulation and pregnancy rates, with weakened power due to limited studies. This is warranted to be further validated and clarified the underlying mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study showed that oral administration of L-carnitine improved the developmental potential and clinical outcome of their oocytes following insemination in patients who failed to conceive. There was no abnormality in Apgar score values and birth weight (Kitano et al, 2018). Another experiment showed that oral L-Carnitine administration with metformin improved the rate of ovulation, pregnancy, and menstrual regulation among clomipheneresistant obese PCOS women (El Sharkwy et al, 2019).…”
Section: In Vivo Experimental Modelsmentioning
confidence: 94%